Which unmet social care needs have the biggest impact on healthy ageing? An analysis of data from the English Longitudinal Study of Ageing - Barbara Hanratty; Gemma F Spiers; David Sinclair; Andrew Kingston; Michelle M C Tan; Laurie E Davies (BMJ Open)
Background and aim Unmet need for social care is linked to numerous adverse health outcomes. Understanding which unmet needs have the biggest impact on healthy ageing could help resource-stretched services prioritise care. To address this evidence gap, our analysis aimed to explore the association between selected individual unmet care needs and an indicator of healthy ageing.Design and data Cross-sectional analysis of data from the English Longitudinal Study of Ageing (Wave 9). A total of 6109 people aged 50 years or over, with complete data items, formed the basis for this analysis.Measures Absolute unmet need for help with each: walking 100 yards and climbing one flight of steps (mobility); managing money, managing medication, doing housework and shopping for groceries (instrumental activities of daily living (IADLs)); and dressing, walking across a room, bathing or showering, eating, using the toilet and getting in and out of bed (activities of daily living (ADLs)). Our outcome measure was poor self-rated health .Results Associations between poor self-rated health and most unmet ADL, IADL and mobility needs were not statistically significant. People with an unmet need for support with managing money were nine times more likely to report poor self-rated health than those whose support needs were met in this domain (OR=9.23, 95% CI: 2.12 to 40.23). In a comparison of people with met and unmet needs, individuals with met needs had higher levels of dependency than those with unmet needs.Conclusions Some unmet needs may be especially consequential for older people’s health. However, shortcomings in current data limit a clear and confident assessment of this. Our analysis highlights the importance of data on the level of need to better understand the link between unmet care needs and healthy ageing.